A Protective and Pathogenic Role for Complement During Acute Toxoplasma gondii Infection - Sikorski, Patricia M.; Commodaro, Alessandra G.; Grigg, Michael E. (Frontiers in Cellular and Infection Microbiology, 2021)
The infection competence of the protozoan pathogen Toxoplasma gondii is critically dependent on the parasite’s ability to inactivate the host complement system. Toxoplasma actively resists complement-mediated killing in non-immune serum by recruiting host-derived complement regulatory proteins C4BP and Factor H (FH) to the parasite surface to inactivate surface-bound C3 and limit formation of the C5b-9 membrane attack complex (MAC). While decreased complement activation on the parasite surface certainly protects Toxoplasma from immediate lysis, the biological effector functions of C3 split products C3b and C3a are maintained, which includes opsonization of the parasite for phagocytosis and potent immunomodulatory effects that promote pro-inflammatory responses and alters mucosal defenses during infection, respectively. In this review, we discuss how complement regulation by Toxoplasma controls parasite burden systemically but drives exacerbated immune responses locally in the gut of genetically susceptible C57BL/6J mice. In effect, Toxoplasma has evolved to strike a balance with the complement system, by inactivating complement to protect the parasite from immediate serum killing, it generates sufficient C3 catabolites that signal through their cognate receptors to stimulate protective immunity. This regulation ultimately controls tachyzoite proliferation and promotes host survival, parasite persistence, and transmissibility to new hosts.